Determination of Technical and Economic Indicators of Road Construction Machines (Texas Journal of Engineering and Technology, 2023)
The technical and economic indicators of road construction machines are studied in this article. Constructive-accounting performance (Pk-h), technical performance (Pt), and operational performance (Pe) were determined